Practice Beyond the Classroom: Vietnamese University Students' Perception of Using Songs to Learn English - Tuan Le (FOSTER: Journal of English Language Teaching, 2023)
English songs are believed to be a helpful tool in teaching and learning English. Literature shows that the use of this vigorous tool not only facilitates students’ language development, but also enlarges their knowledge and motivation to learn. While applying songs in teaching has been widely studied, little is known about what learners think of this practice. The present study was therefore conducted to address this question. The study had a participation of 49 students majoring in English at Can Tho University, Vietnam. Using a questionnaire to survey learners’ opinion, the study found that Vietnamese university students have a positive attitude and high motivation towards listening to English songs in their study outside the classroom. Students’ preference regarding trendy songs and favorite singers and listening challenges were also identified and discussed. The study suggests a number of implications that add to the current literature on songs and their application in education.